A Britten sourcebook - Evans, John; Reed, Philip; Wilson, Paul (Suffolk The Britten-Pears foundation, 1987)
This source book seeks to place in the public domain detail concerning Benjamin Britten's life, public career and compositions which until now was available only in scattered form or known only to those with access to the composer's private papers and composition manuscripts. Contact with primary sources makes it possible, for example, to enumerate for the first time an unprecedentedly detailed list of Britten's vast juvenilia in the chronology. The catalogue raisonne of the composer's incidental music for the media of film, theatre and radio offers a detailed survey of the field and incorporates recent research. The bibliography is the largest since Mitchell and Keller's pioneering work of 1952.